Normal ecumenism: Ecumenism for the long haul1. Issue 1 (February 2019) - Root, Michael
Ecumenical change is best understood as punctuated change, in analogy to change in scientific traditions and in evolution. The ecumenical movement represents a moment of punctuated or revolutionary change in church relations. We are now at the point of the emergence of a new normal, post-revolutionary situation in which further breakthroughs are not to be expected and should not be forced. The challenge will be to preserve our ecumenical commitments in such a new normal. For Catholics especially, ecumenical commitment derives from fundamental theological commitments and cannot be abandoned.